2015
DOI: 10.5219/487
|View full text |Cite
|
Sign up to set email alerts
|

Properties and nutritional value of wheat bread enriched by hemp products

Abstract: Hemp (Cannabis sativa) is annual plant that is native to China and remained as important material for food, industrial and medical purposes. As source of cannabinoids belongs to controversial, but due to its excellent nutritional profile, non-gluten protein, fat and fibre it has potential in bakery products. Addition of 5% - 20% of hemp press cake fine flour and fine wholemeal significantly increased dietary fibre content, but their influence on volume of laboratory baked bread was different. Reflecting actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 2 publications
4
17
0
Order By: Relevance
“…The obtained results showed that the presence of whole hempseeds in the bread dough did not impair the specific bread volume in comparison with the control. A similar finding was noted also by Švec and co-workers [ 169 ] who found that the volume of the bread enriched with whole hempseeds powder (i.e., ground whole hempseeds) was higher than those obtained for the breads enriched with other defatted hempseed products (i.e., hempseed flour or hempseed protein concentrates). This fact has been attributed to the interactions between lipids and proteins and to the influence of the fat in terms of enhancing dough expansion during proofing [ 166 ].…”
Section: Hempseed Foodssupporting
confidence: 88%
See 4 more Smart Citations
“…The obtained results showed that the presence of whole hempseeds in the bread dough did not impair the specific bread volume in comparison with the control. A similar finding was noted also by Švec and co-workers [ 169 ] who found that the volume of the bread enriched with whole hempseeds powder (i.e., ground whole hempseeds) was higher than those obtained for the breads enriched with other defatted hempseed products (i.e., hempseed flour or hempseed protein concentrates). This fact has been attributed to the interactions between lipids and proteins and to the influence of the fat in terms of enhancing dough expansion during proofing [ 166 ].…”
Section: Hempseed Foodssupporting
confidence: 88%
“…In this regard, Pojic and colleagues [ 166 ] showed that the bread volume was significantly impaired as the level of hemp flour increased. This result was found also by Hrušková and co-workers [ 171 ] and by Švec and colleagues [ 169 ] for bread enriched with 10%, 15%, or 20% of hempseed flour, and was confirmed also by Mikulec and others [ 172 ] for bread containing 15%, 30%, or 50% of hempseed flour, as well as by Wang and colleagues [ 173 ] for bread enriched with 5%, 10%, or 15% extruded hemp-rice flour (EHR), made by the extrusion of the whole hempseeds (30%) together with the rice flour (70%). According to the authors, the decrease in the bread’s volume could be due to the partial replacement of wheat flour with a non-glutinous one, that may dilute the gluten protein of wheat flour and prevent its extension, or to the increased content of fibre, which reduces the ability to retain fermentation gases.…”
Section: Hempseed Foodssupporting
confidence: 83%
See 3 more Smart Citations